Nitrogen Advanced Treatment of Urban Sewage by Denitrification Deep-Bed Filter: Removal Performance and Metabolic Pathway - Huang, Xiao; Xing, Yixiao; Wang, Hongjie; Dai, Zhongyi; Chen, Tiantian (Frontiers in Microbiology, 2022)
This study aimed to explore the performance of denitrification deep-bed filter to meet more stringent total nitrogen (TN) discharge standard (10.0 mg L-1 27 ). Operation parameters were optimized for the maximum TN removal efficiency, and microbiological properties were studied for revealing the mechanism of nitrogen removal. The results showed that more than 12.7% TN removal efficiency was obtained by adding methanol compared with the same quality sodium acetate, and the optimal influent C/N ratio and HRT was 3:1 and 0.25 h, respectively, with effluent TN was 6.0-7.0 mg L-1 and COD was 10-15 mg L-1. The backwash time was 12 h under the optimal HRT and the biofilm biomass reduced with filter depth increasing. High throughput sequencing results demonstrated that microbial richness and diversity in middle of filter was higher than both ends. Besides, Proteobacteria, Chloroflexi, Actinobacteria, and Saccharibacteria were dominant flora at phylum level, and Blastocatellaceae_Subgroup_4 and norank_o_JG30-KF-CM45 were dominant denitrification floras with abundance of 6-10%. Meanwhile, the abundance of relative enzyme reached the maximum at 50 cm of this DN-DBF.